Clinical outcome of patients diagnosed with myelodysplastic syndrome-unclassifiable (MDS-U): single center experience. Issue 10 (24th August 2019) - Baidoun, Firas; Chen, Dong; Patnaik, Mrinal; Gangat, Naseema; Begna, Kebede; Elliott, Michelle; Hogan, William; Litzow, Mark; Al-Kali, Aref
Abstract: Myelodysplastic syndrome unclassifiable (MDS-U) is a small subtype of myelodysplastic syndromes (MDS). However, rare literature exists in terms of natural progression and clinical outcome of patients with MDS-U. In the present study, we investigated the characteristics and the clinical outcomes of patients categorized as MDS-U based on 2008 World Health Organization criteria (WHO) in a single center comparing to other MDS groups. Out of eight hundred and two patients who met WHO criteria for MDS at our institution, ninety patients (11%) were initially classified as MDS-U. Upon pathological review, only half of the cases were confirmed to be MDS-U. With follow up, half of the MDS-U cases were reclassified to another subtype. We found neither significant difference in median overall survival nor in risk of transformation to acute myeloid leukemia when comparing MDS-U to other MDS groups. Additional larger studies are needed to confirm our results.